Gene annotation of Linum tenue - Fracassetti, Marco; Slotte, Tanja; Gutiérrez-Valencia, Juanita; Zervakis, Panagiotis-Ioannis; Postel, Zoé; Losvik, Aleksandra; Mehrabi, Sara; Bunikis, Ignas; Soler, Lucile; Hughes, P. William; Désamoré, Aurélie; Laenen, Benjamin; et al. (Stockholm University, 2024)
The file contains the gene annotation of Linum tenue genome.

The genome has been deposited to ENA with the accession id: GCA_946122785 (Project PRJEB52918). See link below.

The gene annotation has been done with MAKER (https://www.yandell-lab.org/software/maker.html) by NBIS. The genes contained in the S-locus region has been manually annotated using StringTie (https://ccb.jhu.edu/software/stringtie/) and TransDecoder (https://github.com/TransDecoder/).

It is part of this article: Gutiérrez-Valencia, J., Zervakis, P. I., Postel, Z., Fracassetti, M., Losvik, A., Mehrabi, S., ... & Slotte, T. (2024). Genetic causes and genomic consequences of breakdown of distyly in Linum trigynum. Molecular Biology and Evolution, msae087. https://doi.org/10.1093/molbev/msae087
Keywords: Evolutionary ecology; Medical and Health Sciences; Medicin och hälsovetenskap; Ecology; Ekologi